Subcutaneous panniculitis-like T-cell lymphoma - Atul Jain; Banyameen Iqbal; Tushar Kambale (Archives of Medicine and Health Sciences, 2014)
Panniculitis like T-cell lymphoma is a rare, aggressive variant of cutaneous T-cell lymphoma. The main dilemma lies in differentiating these lesions from simple panniculitis which is a benign lesion. We present the case of a 73 -year-old female patient, who presented with complaints of swelling in left axilla since 15 days, associated with throbbing pain and swelling of one arm. The initial diagnosis was paniculitis, but no clinical improvement was seen despite systemic antibiotic therapy. After two skin biopsies, the patient was diagnosed with panniculitis cutaneous T-cell lymphoma (PTCL). SPTCL can be a challenge to diagnose and can be misdiagnosed as benign panniculitis due to similarities in clinical and histological features between the two entities and for which immunohistochemical stains are required for confirmation of diagnosis.